Regulatory Barriers Blocking Standardization of Interoperability - Zhong, Daidi; Kirwan, Michael J; Duan, Xiaolian (JMIR Publications, 2013)
Developing and implementing a set of personal health device interoperability standards is key to cultivating a healthy global industry ecosystem. The standardization organizations, including the Institute of Electrical and Electronics Engineers 11073 Personal Health Device Workgroup (IEEE 11073-PHD WG) and Continua Health Alliance, are striving for this purpose. However, factors like the medial device regulation, health policy, and market reality have placed non-technical barriers over the adoption of technical standards throughout the industry. These barriers have significantly impaired the motivations of consumer device vendors who desire to enter the personal health market and the overall success of personal health industry ecosystem. In this paper, we present the affect that these barriers have placed on the health ecosystem. This requires immediate action from policy makers and other stakeholders. The current regulatory policy needs to be updated to reflect the reality and demand of consumer health industry. Our hope is that this paper will draw wide consensus amongst its readers, policy makers, and other stakeholders.